The seasonal periodicity of the diatom Asterionella formosa Hassall in a moderately eutrophic lake - Sen, Bulent (Gebruder Borntraeger, 2006)
Asterionella formosa Hassall, was a conspicuous member of the phytoplankton, with a distinct seasonal cycle, in a moderately eutrophic lake (Shearwater, England). It was present on most occasions. The coldest and the stet illuminated periods were favourable for the growth of this alga. There were two maxima (late winter/spring [the largest and sometimes under ice] and spring/summer). Dissolved silica supported growth until the vernal maximum was achieved but the influence of phosphate was complex. The size of the vernal maxunum was correlated with nitrate availability suggesting that nitrate did not limit growth. The number of cells per colony increased with the vernal development of Asterionella and reached a peak at the vernal maximum.
Keywords: Phytoplankton; Responses; Silicate; Dynamics; Sea